BURHANI DAN BAYANI DALAM DIALEKTIKA ILMU MENUJU EPISTEMOLOGI ISLAM YANG TRANSFORMATIF: - - Lailatul Zuhriyah; Angellita Salsabila Prasidha (Najah Bestari, 2026)
The Islamic epistemological model has so far been dominated by the bayani (textual) and burhani (rational) approaches, which are often positioned in a dichotomous manner. In the contemporary socio-religious context, a single approach has proven to be inadequate to respond to the complexity of the reality of Muslims. This article explores the potential for integrating the two models as a foundation for developing a transformative Islamic epistemology, one that is not only normative but also contextual and offers solutions to the challenges of the present era. Through a qualitative approach with critical literature studies, it was found that the integration of Burhani and Bayani can strengthen the position of Islam as a religion that is intellectually and practically relevant. This study demonstrates that the synergy between reason and text creates space for the emergence of a more inclusive, adaptive, and liberating Islamic epistemology.